2023
DOI: 10.3324/haematol.2022.282252
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and real-world effectiveness of rituximab maintenance in older patients with mantle cell lymphoma: a population-based analysis

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A prospective randomized controlled trial found that R maintenance after BR regimen did not improve PFS and OS in patients with MCL 22 . Recently, two real‐world studies of large samples found that R maintenance after BR regimen had a longer time to the next treatment and OS than the observation group 39,40 . Our results showed that BR+R regimen may have better PFS than BR regimen, but OS did not improve.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A prospective randomized controlled trial found that R maintenance after BR regimen did not improve PFS and OS in patients with MCL 22 . Recently, two real‐world studies of large samples found that R maintenance after BR regimen had a longer time to the next treatment and OS than the observation group 39,40 . Our results showed that BR+R regimen may have better PFS than BR regimen, but OS did not improve.…”
Section: Discussionmentioning
confidence: 49%
“…22 Recently, two real-world studies of large samples found that R maintenance after BR regimen had a longer time to the next treatment and OS than the observation group. 39,40 Our results showed that BR+R regimen may have better PFS than BR regimen, but OS did not improve. A growing body of observational data supports R maintenance after BR therapy in elderly patients with MCL who do not receive autologous stem cell transplantation.…”
Section: Regimenmentioning
confidence: 75%
“…The main limitation of our study is represented by the retrospective nature of the study and the reduced sample size, and this may explain why some classic prognostic factors, such as MIPI score and stage, did not affect PFS and OS in our cohort. Another limitation is that patients did not receive rituximab as maintenance therapy, which may ensure further PFS and OS improvement in future studies [ 10 , 47 ].…”
Section: Discussionmentioning
confidence: 99%